Pengaruh Motivasi Kerja Rotasi Kerja dan Kompensasi terhadap Kinerja Kinerja Karyawan - Nur M. Ridha Tarigan; Tri Kartika Yudha; Muhammad Prasetyo Wibowo; Vira Monica Putri (Manajemen dan Bisnis, 2022)
This research was conducted at PT. Aido Nauli Sibolga which is engaged in retail, where the purpose of this study is to determine the effect of work motivation, job rotation, and compensation on the performance of employees of PT. Aido Nauli Sibolga either simultaneously or partially. The population in this study amounted to 58 employees, so the samples taken were all employees of PT. Aido Nauli Sibolga because the population is less than 100 people. The analysis technique used is descriptive method and quantitative method using the SPSS 20.0 analysis tool. The results of this research simultaneously work motivation, job rotation, and compensation variables have a positive and significant effect on the performance of employees of PT. AidoNauli Sibolga.